A Women's Group-Based Nutrition Behavior Change Intervention in India Has Limited Impacts Amidst Implementation Barriers and a Concurrent National Behavior Change Campaign. (7th June 2021) - Scott, Samuel; Gupta, Shivani; Kumar, Neha; Raghunathan, Kalyani; Thai, Giang; Quisumbing, Agnes; Menon, Purnima
Abstract: Objectives: Women's self-help groups (SHGs) have become one of the world's largest institutional platforms of the poor, reaching over 70 million Indian women in 2020. Limited evidence exists on effects of nutrition interventions through SHGs on maternal and child nutrition outcomes. Methods: The Women Improving Nutrition through Group-based Strategies (WINGS) study was a quasi-experimental impact evaluation, comparing 16 matched blocks where communities were provided support to form SHGs and improve women's livelihoods; 8 blocks (1 in each matched pair) received a 3-year nutrition intervention (NI) with nutrition education, agriculture- and rights-based information, facilitated by a trained female volunteer; the other 8 blocks received standard activities (STD) to support savings & livelihoods. We conducted repeated cross-sectional surveys of mother-child pairs in 2017–18 ( n  = 1609 pairs) and 2019–20 ( n  = 1841 pairs). We matched treatment groups over time and applied difference-in-difference (DID) regression models to estimate NI impacts. Outcomes were knowledge domains (nutrition for pregnant women, breastfeeding, complementary feeding, child health), child feeding (e.g., early breastfeeding initiation, dietary diversity, animal source food (ASF) consumption), woman's diets, woman's BMI and child anthropometry. Matching covariates included woman, child, and community characteristics. Results: About 40% of women were SHG members. Nutrition intervention exposure was low; only ∼10% of NI women had heard of intervention content at endline. There were large improvements in women's knowledge in both groups. DID estimation revealed a positive NI impact on knowledge of timely introduction of ASFs to children ( P  < 0.05), but knowledge of nutrition for pregnant women unexpectedly improved more in the STD group ( P  < 0.05). No impacts were observed for any anthropometry or diet indicators except child ASF consumption ( P  < 0.01). Conclusions: Limited impacts on nutrition outcomes may be due to limited exposure, low motivation or skills of volunteers, and a concurrent national nutrition behavior change program targeting mothers and children in all study areas. Our findings add to a growing literature on SHG-based behavior change interventions and the conditions necessary for their success. Funding Sources: Bill & Melinda Gates Foundation.